Employee Rights and Employer Duties in the Age of Artificial Intelligence: Legal and Organizational Implications - Uzma Abbas (Journal of Advanced Research in HR and Organizational Management, 2025)
Artificial intelligence (AI) is rapidly transforming how organizations manage their employees, from recruitment and evaluation to surveillance and task automation. These technologies promise efficiency and standardization but also challenge established legal and ethical norms that protect workers. This paper examines the key legal and organizational implications of AI adoption in employment. It discusses how AI changes privacy expectations, introduces new forms of algorithmic discrimination, and reshapes employer duties concerning transparency, accountability, and fairness. The paper also highlights the duty to retrain displaced workers, the importance of employee participation in technological change, and the need for updated legal frameworks. The study concludes that responsible AI governance in workplaces must combine human oversight, ethical design, and legal safeguards to protect worker dignity while supporting innovation.